2020
DOI: 10.1371/journal.pmed.1003163
|View full text |Cite
|
Sign up to set email alerts
|

The association of skin autofluorescence with cardiovascular events and all-cause mortality in persons with chronic kidney disease stage 3: A prospective cohort study

Abstract: Background Tissue advanced glycation end product (AGE) accumulation has been proposed as a marker of cumulative metabolic stress that can be assessed noninvasively by measurement of skin autofluorescence (SAF). In persons on haemodialysis, SAF is an independent risk factor for cardiovascular events (CVEs) and all-cause mortality (ACM), but data at earlier stages of chronic kidney disease (CKD) are inconclusive. We investigated SAF as a risk factor for CVEs and ACM in a prospective study of persons with CKD sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Previous studies had reported that lower eGFR was independently associated with death from any cause and HF hospitalization in patients with HF [ 33 ]. Moreover, other studies investigating SAF as a prognostic factor for cardiovascular events and death in patients with earlier stages of CKD revealed that both SAF and higher eGFR were independently associated with a decreased risk of cardiovascular events and death [ 34 ]. Our findings are consistent with those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that lower eGFR was independently associated with death from any cause and HF hospitalization in patients with HF [ 33 ]. Moreover, other studies investigating SAF as a prognostic factor for cardiovascular events and death in patients with earlier stages of CKD revealed that both SAF and higher eGFR were independently associated with a decreased risk of cardiovascular events and death [ 34 ]. Our findings are consistent with those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the pro-oxidant, inflammatory, and uremic environment of CKD and the reduced kidney filtration were among the main causes promoting AGEs synthesis and accumulation [ 27 ]. AGEs are recognized risk factors for the progression of both CKD and other co-morbidities affecting these patients, such as cardiovascular disorders, sarcopenia, and frailty [ 3 , 28 , 29 , 30 , 31 , 32 ]. Furthermore, we have recently shown that AGEs may help to stratify overall mortality risk in patients with advanced CKD [ 7 ], thus emphasizing the importance of AGEs as a biomarker for implementing the clinical evaluation of CKD patients to improve their overall outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing the relationship between SAF and CVD in HD patients are limited and reported that SAF is the independent predictor for overall mortality in HD patients [11,16,17]. However several studies have shown the strong association between SAF, CVD and CKD [18][19][20][21]. For patients on peritoneal dialysis, one study showed that more deaths were observed in group with high SAF than in group with low SAF group.…”
Section: Discussionmentioning
confidence: 99%
“…McIntyre et al reported in a cohort of 1707 patients with CKD class III that a large number of cardiovascular and renal risk factors were associated with SAF, such as eGFR, hemoglobin, smoking, total cholesterol, diastolic blood pressure, c-reactive protein, albuminemia, pulse wave velocity, diabetes, and uremic acid [13]. Recently, Shardlow et al have investigated in a large prospective cohort study that SAF was an independent risk factor for cardiovascular events and all-cause mortality in persons with early CKD [21]. This new nding supports the usefulness of SAF measurement as predictor biomarker for clinicians to detect early disease and monitor patient's health over time.…”
Section: Discussionmentioning
confidence: 99%